2021
DOI: 10.1101/2021.10.10.21264827
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Heterologous SARS-CoV-2 Booster Vaccinations – Preliminary Report

Abstract: Background: While Coronavirus disease 2019 (Covid-19) vaccines are highly effective, breakthrough infections are occurring. Booster vaccinations have recently received emergency use authorization (EUA) for certain populations but are restricted to homologous mRNA vaccines. We evaluated homologous and heterologous booster vaccination in persons who had received an EUA Covid-19 vaccine regimen. Methods: In this phase 1/2 open-label clinical trial conducted at ten U.S. sites, adults who received one of three EUA… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
80
1
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(97 citation statements)
references
References 22 publications
14
80
1
2
Order By: Relevance
“…In immunogenicity studies, heterologous ChAdOx1 followed by mRNA vaccination induced antibody titers exceeding homologous vector vaccination and comparable to homologous mRNA vaccination. [11][12][13] For pragmatic and immunologic reasons, some countries (e.g. France, Germany, Spain, the United Kingdom (UK)) have, like Canada, recommended and accepted mixed schedules as providing valid two-dose protection.…”
Section: Discussionmentioning
confidence: 99%
“…In immunogenicity studies, heterologous ChAdOx1 followed by mRNA vaccination induced antibody titers exceeding homologous vector vaccination and comparable to homologous mRNA vaccination. [11][12][13] For pragmatic and immunologic reasons, some countries (e.g. France, Germany, Spain, the United Kingdom (UK)) have, like Canada, recommended and accepted mixed schedules as providing valid two-dose protection.…”
Section: Discussionmentioning
confidence: 99%
“…Protection after the third dose would be substantially stronger across all the scenarios considered, given the likely neutralisation increase relative to the second dose. In fact, the assumed 3.3-fold increase could be too conservative, given the 20x (15, 27) increase reported in Atmar et al [2021] for homological Comirnaty boosting, and the 25x increase from the early data in Pfizer/BioNTech [2021] on Omicron pseudovirus neutralisation. The symptomatic effectiveness, predicted here for general adult populations, is likely to be higher in adolescents and young adults.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have assessed the safety and immunogenicity of heterologous prime-boost regimens involving different vaccine platforms. A recent study involving individuals who originally received one of the three EUA vaccines (mRNA-1273, Ad26.COV2.S, or BNT162b2) and were subsequently boosted with a homologous or heterologous vaccine suggests that both boosting schedules increase protective efficacy against symptomatic SARS-CoV-2 infection [39]. In a separate study, favorable increases in humoral responses were observed in individuals previously vaccinated with the ChAdOx1 nCoV-19 vaccine and subsequently boosted with BNT162b2 [40, 41].…”
Section: Discussionmentioning
confidence: 99%